2018
DOI: 10.1093/infdis/jiy579
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Cellular Niches for Mycobacterium tuberculosis in Latent Tuberculosis Infection

Abstract: Latent tuberculosis has been recognized for over a century, but discovery of new niches, where Mycobacterium tuberculosis resides, continues. We evaluated literature on M.tuberculosis locations during latency, highlighting that mesenchymal and hematopoietic stem cells harbor organisms in sensitized asymptomatic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 78 publications
5
41
0
Order By: Relevance
“…2017) and bone marrow (Mayito et al . 2019) have been proposed as extrapulmonary niches where the tubercle bacillus could persist for long periods of time modulating the local tissue environment.…”
Section: From Tissues To Phagosomes: the Environments Mtb Faces In Thmentioning
confidence: 99%
“…2017) and bone marrow (Mayito et al . 2019) have been proposed as extrapulmonary niches where the tubercle bacillus could persist for long periods of time modulating the local tissue environment.…”
Section: From Tissues To Phagosomes: the Environments Mtb Faces In Thmentioning
confidence: 99%
“…The hypoxic microenvironment of stem cell niche may favor Mtb dormancy ( 76 , 77 ) and resistance against anti TB drugs ( 56 , 57 ). All these reasons unite to make BM stem cells a potential niche for Mtb during LTBI ( 27 ). Interestingly, stem cell’s self-renewal property is utilized by other bacteria, including Mycobacterium leprae ( 78 ) and Wolbachia ( 79 ) for effective transmission.…”
Section: Bone Marrow (Bm) Stem Cell Niche As the Site Of Dormant mentioning
confidence: 99%
“…Following our initial findings, many laboratories not only reproduced our findings but also added important information about the Mtb /human BM-stem cell host-pathogen interaction ( 24 26 ). These findings raise human bone marrow derived stem cells as the site of Mtb latency ( 27 ). Recently, we have shown that stem cell altruism may be involved in Mtb -reactivation ( 28 ), and in the aerosol-induced immunity ( 29 ).…”
Section: Introductionmentioning
confidence: 95%
“…Mtb-specific CD4+ T-cell activation markers in blood may discriminate pulmonary and extrapulmonary TB from LTBI (Silveira-Mattos et al, 2019). Recently, Mtb has been demonstrated in mesenchymal and hematopoietic stem cells (Mayito et al, 2019); thus whole genome sequencing of bone marrow specimens from LTBI patients may show the presence of Mtb with rpo gene mutations in stem cell CD34 populations.…”
Section: Advancing Ltbi Diagnostic Testsmentioning
confidence: 99%